Antinociceptive and Anxiolytic and Sedative Effects of Methanol Extract of Anisomeles indica: An Experimental Assessment in Mice and Computer Aided Models - Uddin, Md. Josim; Ali Reza, A. S. M.; Abdullah-Al-Mamun, Md.; Kabir, Mohammad S. H.; Nasrin, Mst. Samima; Akhter, Sharmin; Arman, Md. Saiful Islam; Rahman, Md. Atiar (Frontiers in Pharmacology, 2018)
Anisomeles indica (L.) kuntze is widely used in folk medicine against various disorders including allergy, sores, inflammation, and fever. This research investigated the antinociceptive, anxiolytic and sedative effects of A. indica methanol extract. The antinociceptive activity was assessed with the acetic acid-induced writhing test and formalin-induced flicking test while sedative effects with open field and hole cross tests and anxiolytic effects with elevated plus maze (EPM) and thiopental-induced sleeping time tests were assayed. Computer aided (pass prediction, docking) analyses were undertaken to find out the best-fit phytoconstituent of total fourteen isolated compounds of this plant for aforesaid effects. Acetic acid treated mice taking different concentrations of extract (50, 100, and 200 mg/kg, intraperitoneal) displayed reduced the writhing number. In the formalin-induced test, extract minimized the paw licking time of mice during the first phase and the second phase significantly. The open field and hole-cross tests were noticed with a dose-dependent reduction of locomotor activity. The EPM test demonstrated an increase of time spent percentage in open arms. Methanol extract potentiated the effect of thiopental-induced hypnosis in lesser extent comparing with Diazepam. The results may account for the use of Anisomeles indica as an alternative treatment of antinociception and neuropharmacological abnormalities with further intensive studies. The compound, 3,4-dihydroxybenzoic acid was found to be most effective in computer aided models.